Organisation of Commerce Std XII - Nagwekar, K G; Gite ,S R; Vachharajani ,K S; Vachharajani, K. S.; Nagwekar, K. G.; Gite, S. R.; Rangparia, A. N. (Pune sheth publication, 2003)
Forms Of Commercial Organisation .